Pengaruh Media Audio-visual dalam Pemerolehan Bahasa Korea bagi Orang Dewasa - Triswanto, Ririn Marlina (Kampret Journal, 2024)
Language is never separated from humans, so there is no human activity that is not accompanied by language. Humans are also learning creatures, so their high curiosity leads humans to find out the things they want to know. Humans acquire their first language naturally and unintentionally, in contrast to the acquisition of a second language which is done consciously and intentionally. In acquiring language, humans also cannot be separated from the ability that they can use two languages simultaneously, known as bilingualism. This study was conducted to determine the effect of audio-visual media in foreign language acquisition, especially Korean for adults, influencing factors, and learning methods that affect language acquisition. It was found that adulthood does not prevent a person from learning a new language especially aided by the case study method and environmental factors that support language learning. In addition, the environment of study, work and home also influences second language learning.